Resource nationalism and local empowerment: the case of Zvishavane Community Share Ownership Trust, 2012 to 2017 - Mafunga, Faith (Midlands State University, 2019)
Zvishavane district has been characterized by poor roads, water problems, food shortages, poor health delivery, poor educational facilities and high rate of unemployment despite the fact that the district is rich in precious minerals such as gold, platinum and diamond. This has been the case in many mining towns in Zimbabwe. In an effort to nationalize the country’s natural resources, the Zimbabwean government adopted the Indigenization and Economic Empowerment (IEE) policy in 2007 which later gave birth to Community Share Ownership Trusts (CSOT) in 2011.The scheme was introduced to make sure the local communities participate in the distribution of the country’s natural wealth leading to socioeconomic development in the area. However there are still socio-economic challenges in the Zvishavane District and the research seeks to investigate the effectiveness of Zvishavane Community Share Ownership Trust (ZCSOT) in promoting resource nationalism and local empowerment in the district since 2012 to 2017. During the research data was collected through interviews with ZCSOT members and the community members in the district. The study traced the history of mining in Zvishavane district before the establishment of ZCSOT and it was clear that the local people did not benefit much from the mining activities in the district. The study also looked at the initiatives of ZCSOT and its challenges. The research ended by looking at the community’s perception of the ZCSOT and it was clear to understand that the community lacks knowledge about the organization. Lack of information about the Trust among the community members had hindered development in the district as many community members do not know their rights in the organization. This has also led to limited community’s participation in the development process.